2015
DOI: 10.1080/0309877x.2015.1062851
|View full text |Cite
|
Sign up to set email alerts
|

Using the assessment process to overcome Imposter Syndrome in mature students

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 34 publications
1
37
0
2
Order By: Relevance
“…Chance and Imes' research sample group included high achieving women in academia from undergraduates to faculty members. Other research since then has identified this inability to internalize accomplishments and its adverse effect on academic performance in a variety of student groups including: mature students (Chapman, 2015), ethnic minority students (Peteet, Montgomery and Weekes, 2015), and first generation students (Gardner and Holley, 2011), among others.…”
mentioning
confidence: 99%
“…Chance and Imes' research sample group included high achieving women in academia from undergraduates to faculty members. Other research since then has identified this inability to internalize accomplishments and its adverse effect on academic performance in a variety of student groups including: mature students (Chapman, 2015), ethnic minority students (Peteet, Montgomery and Weekes, 2015), and first generation students (Gardner and Holley, 2011), among others.…”
mentioning
confidence: 99%
“…Within Ed.D. programs, mentoring is often seen as a barrier to retention as it fulfills a need to belong within an academic setting that can feel foreign (Chapman, 2017;Coryell et al, 2013). Through frequent interaction, a positive nature, and being centered on positive concern for another, mentoring, particularly for scholarpractitioners in Ed.D.…”
Section: Resultsmentioning
confidence: 99%
“…candidates work full time as leaders within their professional roles. These individuals are educational leaders who have a strong sense of self and identity within their work; however, they may not have a clear sense of what the identity of a researcher and scholar may be (Chapman, 2017;Hall & Burns, 2009).…”
Section: The Importance Of Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Research can be seen for academics in general (Knights & Clarke, 2014;Hutchins, 2015), minorities (Muhs, Niemann, González, & Harris, 2012;Earle Reybold & Alamia, 2008;Craddock, Birnbaum, Rodriguez, Cobb, & Zeeh, 2011;Farrel, Alabi, Whaley, & Jenda, 2017), mature students (Chapman, 2017;Johnson, 2004), and undergraduate and graduate students (Kolligian & Sternberg, 1991;Ewing, Richardson, James-Myers, & Russell, 1996;Craddock, Birnbaum, Rodriguez, Cobb, & Zeeh, 2011). These examples work in conjunction with other variables, but demonstrate that librarianship is not unique in terms of experiences of IS.…”
mentioning
confidence: 99%